A teaching note on the tax benefits of retirement savings. Issue 2 (June 2015) - Schwartz, Steven T.; Spires, Eric E.; Young, Richard A.
Highlights Textbook treatment of retirement savings often focuses on technical details. A fundamental analysis of the tax benefits of retirement savings is presented. Four interacting benefits are identified; three derive from deferred taxation, while one is a product of tax code progressivity. A problem of deciding how to allocate equity and bond investments is analyzed. Classroom implementation issues are discussed.